KEABSAHAN PERJANJIAN JUAL BELI TANAH DARI OBJEK TANAH WARISAN YANG BELUM DIBAGI BERDASARKAN KUHPERDATA - Alyssa Adelia (Jurnal Interpretasi Hukum, 2024)
Complex problems often occur in the process of transferring inherited property in the form of inherited land rights. Legal disputes may still occur in the sale and purchase agreement of inherited land that has received a sale and purchase deed made by a PPAT if the agreement does not meet the requirements in accordance with the provisions of the applicable laws and regulations. The purpose of this research is to analyze and find out the consequences of the validity of the sale and purchase agreement of inherited land that has not been divided based on the legal requirements of the agreement as regulated in Article 1320 of the Civil Code. This research method uses normative research conducted using literature studies and uses secondary data sources, which include primary legal materials in the form of the Civil Code, Government Regulation Number 24 of 1997 concerning land registration, and Law Number 30 of 2004 concerning notary offices. As well as secondary legal materials, namely literature, relevant scientific articles, and court decisions. The data is then analyzed using qualitative analysis, namely analyzing material with descriptive writing techniques by explaining in detail and systematically solving problems. The results of this study indicate that the validity of the agreement to sell and purchase undivided inherited land among the heirs of the late WO is invalid because one of the requirements of the agreement stipulated in Article 1320 of the Civil Code is not fulfilled, and the legal remedies that can be taken by the heirs whose rights have been harmed are to file a lawsuit or receive compensation.